sistem informasi monitoring kerja praktek di universitas wijaya kusuma surabaya - Kevin Panji Wicakono; Shofiya Syidada (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2021)
Wijaya Kusuma University Surabaya is a private campus located in the Dukuh Kupang area. The registration and monitoring system for practical work is not effective, where student administration is still manual. Therefore, the Job Training Monitoring Information System at Wijaya Kusuma University Surabaya is designed to facilitate the administration of practical work on campus such as registration of practical work via a web designed, assistance to lecturers can be done online, and can upload reports of practical work done. The information system created is based on a website and programming language, which is used is PHP and database.. which is used is MySQL. The software methodology uses Waterfall. The result of this system is that it can help students provide assistance to their supervisors. Keywords: smart campus information system, practical work, PHP, MySQL, waterfall